Promising in vitro performances of nickel-free nitrogen containing stainless steels for orthopaedic applications - Talha M.; Behera C.K.; Sinha O.P. (My University, 2025)
The aim of the present work was to study the in vitro corrosion resistance in Hank's solution and biocompatibility of indigenized low-cost Ni-free nitrogen containing austenitic stainless steels (HNSs) and to compare with conventionally used 316L and 316LVM. The electrochemical behaviour was assessed using electrochemical impedance spectroscopy, potentiostatic polarization and scanning electron microscopy. The MTT assay [3-(4,5-dimethythiazol 2-yl)-2,5-diphenyltetrazolium bromide] was performed using Dalton's lymphoma cell line for cytotoxicity evaluation and cell adhesion test. The resistance of surface film was raised by increasing nitrogen content in stainless steel (SS). The corrosion current density was decreased with increase in nitrogen content and corrosion potentials for HNS were observed to be more positive. Shallower and smaller pits were associated with HNS, indicating that nitrogen suppresses the pit formation. The HNS had higher cell proliferation and cell growth and it increases by increasing the nitrogen content. The surface wettability of the alloys was also investigated by water contact-angle measurements. The value of contact angles was found to decrease with increase in nitrogen content. This indicates that the hydrophilic character increases with increasing nitrogen content, which is further attributed to enhance the surface free energy that would be conducive to cell adhesion, which in turn increases the cell proliferation. © Indian Academy of Sciences.